Raising the global floor. Dismantling the myth that we can't afford good working conditions for everyone - Heymann, Jody; Earle, Alison (Stanford, 2010)
"News stories on the impact of job loss appear daily in the media. Less reported is that working conditions in many countries around the world have deteriorated as rapidly as jobs have been lost--and this affects ten times as many people. Working conditions significantly impact our health, the amount of time we can spend with family, our options during momentous life events (such as the birth of a child or the death of a parent), and whether we keep or lose a job when the unexpected occurs. Inexplicably, the global community has nearly universally accepted the argument that any country that guarantees a floor of decent working conditions will suffer higher unemployment and will be less competitive. Raising the Global Floor shatters this widely held view by presenting the first ever, global analysis of the relationship between labor conditions, national competitiveness, and unemployment rates in 190 countries. The authors' findings are dramatic. They show that there is no relationship between unemployment rates and providing basic protections in a series of critical areas. Strikingly, data also indicate that good working conditions can make countries more competitive. There are no long-term economic gains to be had if workers are denied paid sick leave, paid annual leave, paid parental leave, the right to a day of rest, and many other basic protections that would improve the quality of their lives."